The Implementation of Free Writing Paragraph on Student’s Writing Skill at the Seventh Grade of MTsN Parteker Pamekasan - Muttaqiin, Miftahul; Halim, Abdul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
This study aims to find the implementation of free writing paragraph to the students’ writing skill and measure the effectiveness of free writing paragraph to their writing skill. The variables in this study are; independent variable is free writing paragraph and dependent variable is the students’ writing skill. The design in this study is pre-experimental design (pre-test and post-test), while the approach is quantitative research. Test and documentation are used as the instruments, while the researcher takes one class as a sample of the study. Test was used to know students’ writing skill and to measure how significance is the effect of using free writing paragraph on students’ writing skill at the seventh grade of MTsN Parteker Pamekasan. The result has shown that the implementation free writing paragraph on students’ writing skill has statistically significant effect, confirmed with t-value is higher than t-table either in 5%, or 1% (5% = 2, 05 < 10,017) or (1% = 2,76 < 10,017). The finding conveys that free writing paragraph can be a choice for teachers to motivate their students in English learning, especially in writing class.